Aspectos da qualidade de vida no trabalho após infecção por Covid-19: um estudo com o TQWL-42 - Cruz, Juliana Sobreira da (2023)
Introduction - The COVID-19infection brought several impacts that affected worker health and Quality of Life at Work. As a result, taking into account that the worker must be the focus, as he is more vulnerable and susceptible to diseases, the Quality of Life of Workers must be a priority for business organizations and the State. For this research, the guiding question is urgent: what are the main factors that influence Quality of Life at Work after COVID-19 infection? Objective- We seek to analyze the aspects that influence Quality of Life at Work after COVID-19 infection. Method - Study with a quantitative-qualitative and descriptive approach, carried out with workers who were hospitalized due to COVID-19 in the years 2020, 2021 and 2022, returned to work and are residents of the Brazilian nation. The research took place in two stages: the first was the online application of the Total Quality of Work Life (TQWL-42) questionnaire, analyzed using scores ranging from 0 to 100. The second stage consisted of the online application of a questionnaire , containing four essay questions in order to present the main aspects such as physical, cognitive and/or psychiatric disorders that lead to prolonged recovery and possible impairment of Quality of Life at Work. Results - This study originated two articles that uniquely understood the QWL of workers after COVID-19 infection, the instrument allowed us to better understand the QWL of these professionals. These scores illustrate the relevance of Quality of Life at Work after COVID-19 infection, instigating a deeper reflection on your Quality of Life, which communicated with the Aspects of TQWL-42, and jointly showed that although there are problems that interfere with QWL such as work capacity, task significance; autonomy; work conditions; Task variety and task identity are, paradoxically, satisfactory. Conclusion - By associating workers' narratives about QWL with the Aspects measured in the TQWL-42 questionnaire, it was demonstrated that QWL was classified as 'good'. The validated instrument showed that self-assessment of QWL can result in important aspects that evaluate workers' lives in general, without intending to exhaust all the factors and variables that make up QWL. The analysis of the answers to the essay questionnaire shows that the participants report some limitations, however, they say they are capable of carrying out their work activities, and the fact that they have become accustomed to the situation does not mean that they have a good Quality of Life, and very It will probably compromise your Quality of Life at Work.